Applying the mixed-blessings model and labeling theory to stigma in inclusive education: An experimental study of student and trainee teachers’ perceptions of pupils with ADHD, DLD, and intellectual disability - Röhm, Alexander; Grengel, Michelle; Möhring, Michélle; Zensen-Möhring, Johannes; Nellen, Cosima; Hastall, Matthias R. (Frontiers in Psychology, 2022)
Institutional and individual stigmatization represent major barriers that prevent children with disabilities from accessing education. It can be presumed that children with disabilities are labeled as such even in inclusive educational settings and that teachers’ attitudes toward inclusive education and children with disabilities play a crucial role in this context. Against this background, the present study aims to (a) apply and conceptualize the mixed-blessings model in the context of stigma-related reactions to children’s disability labels in inclusive education and (b) shed light on the causal attributions of teachers that underlie stigma-related attitudes toward children with various disabilities. A 3 × 2 × 2 × 2 × 2 online experiment examined the ways in which disability-specific causes and symptoms, the type of disability in question, the children’s sex, and efficacy cues regarding educational efforts affect future teachers’ attitudes toward and expectations of inclusive education as well as their social distance toward children with disabilities. The participants in this experiment were N = 605 German student and trainee teachers representing different types of teaching professions. A multivariate analysis of variance (MANOVA) revealed that, in particular, the cause attributed to the disability, the depicted type of disability and the probability of learning success led to changes in attitudes. Respondents’ teaching self-efficacy and their status as students or trainees emerged as moderators of the effect of pupils’ type of disability. As a result, teacher education and training as well as communication regarding pupils with disabilities require a high degree of sensitivity to disability-specific and efficacy-related cues to prevent (accidental) professional or institutional stigmatization.